Genetic diversity and phylogeographic structure of Bactrian camels shown by mitochondrial sequence variations. (24th October 2016) - Ming, L.; Yi, L.; Sa, R.; Wang, Z. X.; Wang, Z.; Ji, R.
Summary: The Bactrian camel includes various domestic ( Camelus bactrianus ) and wild ( Camelus ferus ) breeds that are important for transportation and for their nutritional value. However, there is a lack of extensive information on their genetic diversity and phylogeographic structure. Here, we studied these parameters by examining an 809‐bp mtDNA fragment from 113 individuals, representing 11 domestic breeds, one wild breed and two hybrid individuals. We found 15 different haplotypes, and the phylogenetic analysis suggests that domestic and wild Bactrian camels have two distinct lineages. The analysis of molecular variance placed most of the genetic variance (90.14%, P  <   0.01) between wild and domestic camel lineages, suggesting that domestic and wild Bactrian camel do not have the same maternal origin. The analysis of domestic Bactrian camels from different geographical locations found there was no significant genetic divergence in China, Russia and Mongolia. This suggests a strong gene flow due to wide movement of domestic Bactrian camels.